ANALYSIS OF MARGINALITY INDICATORS BASED ON INTERNATIONAL FINANCIAL REPORTING STANDARDS - Tojiboeva Sh.A. (Scholar Express Journals, 2026)
This article examines the analysis of margins based on international financial reporting standards. Margins are an important criterion for assessing the success of a company's core business. The author shows that by examining the indicator in dynamics, one can see how the company is trying to develop its business and improve margin indicators by increasing the level of these coefficients. The results of the study allow for an accurate assessment of the company's financial performance based on the identification of internal economic opportunities for increasing margins, enhancing investment attractiveness, and ensuring the stability of the financial position.
Keywords: international financial reporting standards; financial reporting; financial results